2019
DOI: 10.26858/eltww.v6i2.10515
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students’ Perspective on the Usefulness of ICT based Learning in Indonesian Higher Education

Abstract: The study explores the perception of the EFL students in English Language Teaching through ICT based learning at Universitas Negeri Makassar. It employs a descriptive study using purposive sampling techniques by taking 57 respondents from university students. The online questionnaire used to collect data on the perception of students on the ICT based Learning of English Language Teaching. The method of descriptive in terms of percentage has been used for data processing, and the deduction method has been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…Considering the mean score of the data analysis, it can be concluded that the students tend to use online collaborative platforms for a critical reading course. The questionnaire was adapted from Davis, 1989;Basri &Paramma, 2019 andWiyaka et.al., 2018 consisting PEU, PU, ATU and BIU. The questionnaire explored about technology accepted model which was implemented for online learning.…”
Section: Finding and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Considering the mean score of the data analysis, it can be concluded that the students tend to use online collaborative platforms for a critical reading course. The questionnaire was adapted from Davis, 1989;Basri &Paramma, 2019 andWiyaka et.al., 2018 consisting PEU, PU, ATU and BIU. The questionnaire explored about technology accepted model which was implemented for online learning.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Attitude towards Usage (ATU) represents individuals' evaluative feelings (positive or negative) when performing a particular behavior (Basri & Paramma, 2019). ATU determines the intention to use a specific program or learning tool.…”
Section: Finding and Discussionmentioning
confidence: 99%
See 3 more Smart Citations